Revitalization of religious narratives for water resource preservation: A case study of Mori indigenous community, Central Sulawesi - Kulla, Selfitriani; Bagir, Zainal Abidin; Northcott, Michael Stanford (Universitas Trunojoyo Madura, 2024)
Water pollution, caused primarily by mining and palm oil plantation, contributed to the water crisis in North Morowali, Central Sulawesi, Indonesia. It has impacted the Mori Indigenous community, which are among the largest and the oldest communities in the area. They have their own ecological knowledge that reveals a strong connection to the water, but the extractive industries, which pollute their historic Tiu Lake, threaten others water resources, and disconnect them from nature. This study examines Mori Indigenous religious narratives of water and how they perceive and cope with the water pollution. This study applies the qualitative research methodology, using in-depth interview and direct observation to collect the data. Employing Indigenous religion paradigm and the theories of sacred natural sites, this study finds that the religious narratives of water are: Tiu Lake Legend, Imbu-the water protector myth, and the sacred place of water resources. They reveal the inter-subjective relationship of the Mori Indigenous community to the water with religious principle such as: the responsible dimension, how they protected Tiu Lake and water resources as sacred place; the ethics dimension is about the rules on water resources; and the reciprocal dimension where they try to maintain a balance and harmony between human and nature. All this ecological knowledge will be used for water resource preservation in North Morowali, Central Sulawesi.